Inside Informality : The Links between Poverty, Microenterprises, and Living Conditions in Nairobi's Slums - Gulyani, Sumila (2012)
Using households rather than enterprises as the analytical unit, this study of 1,755 households in Nairobi's slums reveals that informal household microenterprises are indeed helping offset poverty. Microenterprises are helping households that are, a priori, more likely to be poor. Better microenterprise performance is associated with certain "business-related" factors, such as sales area, time in, and sector of operation. But "living conditions"--residential tenure and infrastructure access--also strongly influence both creation and success of microenterprises. Interventions that improve infrastructure and reduce tenure insecurity and rent-induced pressures to move may be crucial for incubating microenterprises and reinforcing their contribution to poverty alleviation in Nairobi's slums.